2016
DOI: 10.1136/bmjopen-2016-012819
|View full text |Cite|
|
Sign up to set email alerts
|

The Challenge of Universal Eye Health in Latin America: distributive inequality of ophthalmologists in 14 countries

Abstract: BackgroundNo comprehensive study currently exists on the supply of ophthalmologists across Latin America. We explored sociogeographic inequalities in the availability and distribution of ophthalmologists across 14 Latin American countries.MethodsThe National Ophthalmologic Societies of Argentina, Bolivia, Brazil, Colombia, Costa Rica, Chile, the Dominican Republic, Ecuador, Guatemala, Mexico, Paraguay, Peru, Uruguay and Venezuela provided data on affiliated ophthalmologists by first-order subnational divisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
0
29
1
3
Order By: Relevance
“…9 The number of ophthalmologists per million people varied with socioeconomic development, with higher concentration in regions with higher HDI and per capita gross domestic product. [19][20][21] Globally, the preoperative visual acuity with regard to cataract surgery was associated with increasing HDI and per capita income. 22,23 The cost was the main barrier to utilization of cataract surgery in some developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…9 The number of ophthalmologists per million people varied with socioeconomic development, with higher concentration in regions with higher HDI and per capita gross domestic product. [19][20][21] Globally, the preoperative visual acuity with regard to cataract surgery was associated with increasing HDI and per capita income. 22,23 The cost was the main barrier to utilization of cataract surgery in some developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of human resources in eye health in sub-Saharan Africa and Latin America have confirmed these trends of poor distribution and the inability of the cadre to keep up with the population rates. [4][5][6][7] Amidst technological advances, population demand patterns and evolving models of care, complete data for eye health professionals is an integral component to understanding if we can meet the needs of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer than one-third of cataract surgeries were performed in public hospitals. The number and availability of ophthalmologists is an issue in Guatemala (7) . Not only is the number of ophthalmologists per capita considerably below the Latin American average, but they are highly concentrated in the wealthiest areas of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The country has an estimated 1.3 ophthalmologists per 100,000 people, and most opthalmologists practice in Gua temala City. The average for Latin America is 5.2 ophthalmologists per 100,000 people (7) .…”
Section: Introductionmentioning
confidence: 99%